Precise Localization of Dysfunctional Areas in Vertebrobasilar Infarction by FDGand 0-15-H20-PET Using Standardized Image Analysis and Image Registration to 3-D MR - Juengling, F. D.; Kassubek, J.; Moser, E.; Nitzsche, E. U. (Nuklearmedizin - NuclearMedicine, 1999)
The advantages of standardized multimodal image analysis are demonstrated in a case of symptomatic tremor after basilar thrombosis. Functionally and structurally lesioned areas were mapped in Talairach space using 3-D MRI, cerebral FDG-PET and 0-15-H20-PET. Structural lesions were found in the left midbrain, thalamus, putamen and cerebellar areas. Voxel-based statistics in comparison to a normal data base revealed hypometabolism in the left thalamus, left red nucleus, left cerebellar hemisphere including dentate nucleus and in the left inferior olivary nucleus. The 0-15-H20-PET investigation revealed metabolic uncoupling along the rubroolivocerebellar loop. Given the delicate anatomy of the structures involved, image registration and standardized image analysis techniques are essential for a synoptic multimodality analysis of morphological and functional pathology and should generally be used for cerebral PET investigations.
Keywords: MRI; FDG-PET; 0-15-H20-PET; image registration